Chromosomal polymorphism and comparative chromosome painting in the rufous-collared sparrow (Zonotrichia capensis) - Bulau, Sandra Eloisa (2018)
Zonotrichia capensis is widely distributed in the Neotropics. Previous cytogenetic studies demonstrated the presence of polymorphisms in two chromosome pairs (ZCA2 and ZCA4). Here, we report results based on comparative chromosome painting, using probes derived from Gallus gallus and Leucopternis albicollis, focused on characterizing the chromosome organization of Z. capensis. Our results demonstrate the conservation of ancestral syntenies as observed previously in other species of passerine. Syntenies were rearranged by a series of inversions in the second chromosome as described in other Passeriformes, but in this species, by using probes derived from L. albicollis we observed an extra inversion in the second chromosome that had not previously been reported. We also report a paracentric inversion in pair 3; this chromosome corresponds to the second chromosome in Zonotrichia albicollis and may indicate the presence of ancestral inversions in the genus. The chromosomal inversions we found might be important for understanding the phenotypic variation that exists throughout the distribution of Z. capensis.